Exercise-Based Renal Rehabilitation: A Bibliometric Analysis From 1969 to 2021 - Zhang, Fan; Ye, Jing; Bai, Yan; Wang, Hui; Wang, Weiqiong (Frontiers in Medicine, 2022)
Chronic kidney disease (CKD) is a growing global health challenge, with an increasing incidence. Exercise-based renal rehabilitation is an evidence-based, multidisciplinary, and comprehensive intervention designed to improve the physical and psychological condition of patients with CKD. The knowledge structure, research hotspots, and development trends in exercise-based renal rehabilitation have not been systematically described. This study aims to provide a bibliometric perspective of the progress in this field. Publications about exercise-based renal rehabilitation were retrieved from the Web of Science Core Collection, using "exercise," "physical activity," and "chronic kidney disease." Annual publications, subject categories, countries, authors, references, and keywords in this field were visually analyzed using the Citespace, VOSview, and Excel software. A total of 4,610 publications were analyzed, with a steady increase in publications in the field. Overall, the USA is the major contributor to the study of exercise-based renal rehabilitation. Johansen KL and Painter P are the key researchers in this field. Keyword analysis shows that research hotspots in this field include exercise/physical activity for different stages of CKD, exercise-based renal rehabilitation for frailty, and physical activity management for CKD. These findings will better understand exercise-based renal rehabilitation research and inform future research ideas.